Phosphorus-free impregnation method for graphite roller sleeves

Through the phosphorus-free antioxidant impregnation method, an impregnation liquid synthesized by silica sol and α alumina micropowder is used to form an aluminum silicate antioxidant protective film, which solves the problem of oxidation of graphite roller sleeve in a high-temperature environment, and significantly improves its antioxidant performance and service life.

CN116462530BActive Publication Date: 2025-03-11BAOSHAN IRON & STEEL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210031788.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-01-12
Publication Date
2025-03-11
Estimated Expiration
2042-01-12

AI Technical Summary

Technical Problem

Graphite roller sleeves are prone to oxidation in high temperature environments, resulting in loose structure, reduced strength and shortened service life, affecting the quality of strip steel products and production equipment efficiency.

Method used

The phosphorus-free antioxidant impregnation method is adopted to synthesize the phosphorus-free antioxidant impregnation liquid through silicon sol, α-alumina micropowder and dispersant. Using vacuum pressurized impregnation technology, silicon and alumina fully penetrate into the inside of the graphite roller sleeve through the pores, and an aluminum silicate antioxidant protective film is formed on the surface.

Benefits of technology

In high temperature environment, the oxidation weight loss rate of the graphite roller sleeve is significantly reduced, its oxidation resistance is improved, its service life is extended, the stability of the metal roller core and graphite roller sleeve is enhanced, and the production efficiency of silicon steel units is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116462530B_ABST
    Figure CN116462530B_ABST
Patent Text Reader

Abstract

The invention discloses a phosphorus-free impregnation method for a graphite roller sleeve, comprising the steps of: 1. using silica sol as a matrix, adding alpha alumina powder and a dispersant to form a phosphorus-free antioxidant impregnation liquid; 2. heating the phosphorus-free antioxidant impregnation liquid; 3. roughening the surface of the graphite roller sleeve and heating the graphite roller sleeve; 4. evacuating an impregnation tank and injecting the phosphorus-free antioxidant impregnation liquid, and pressurizing the graphite roller sleeve with the phosphorus-free antioxidant impregnation liquid to fully penetrate the inside of the graphite roller sleeve through the pores of the graphite roller sleeve, and forming an aluminum silicate antioxidant protective film on the surface of the graphite roller sleeve; 5. taking out and cooling the graphite roller sleeve; 6. repeating steps 2-4; 7. taking out the graphite roller sleeve and curing the aluminum silicate antioxidant protective film, and the aluminum silicate antioxidant protective film is evenly attached to the inside and surface of the pores of the graphite roller sleeve. The invention can evenly attach the aluminum silicate antioxidant protective film to the surface and inside the pores of the graphite roller sleeve, thereby improving the high-temperature antioxidant performance of the graphite roller sleeve.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a processing technology of a graphite roller sleeve for a heat treatment furnace, in particular to a phosphorus-free impregnation method of the graphite roller sleeve. Background Art

[0002] Graphite roller sleeves are key components in heat treatment furnaces used in silicon steel production. Graphite roller sleeves are distributed along the direction of the strip moving in the heat treatment furnace and are set perpendicular to the direction of the strip moving. The graphite roller sleeves are driven to rotate by a mechanical transmission roller core. The graphite roller sleeves and strip steel are heated to above 1000°C in the heat treatment furnace simultaneously. Due to process requirements and environmental influences, there are oxidizing media such as oxygen and moisture in the heat treatment furnace. The oxidizing media produce severe oxidation effects on the graphite roller sleeves at high temperatures, resulting in loose structure, reduced strength, and shortened service life. The strip steel moves across the surface of the graphite roller sleeves, and the degree of oxidation of the graphite roller sleeves directly affects the product quality of the strip steel, and also affects the operating efficiency of the strip steel production equipment.

[0003] In order to improve the service life of graphite roller sleeves, the main methods for improving the anti-oxidation performance of graphite roller sleeves in the prior art are:

[0004] 1. Impregnation of graphite roller sleeve with oxide solution: Ceramic fine powder is dispersed in a solution according to a certain ratio to form a ceramic colloidal solution, and then the ceramic colloidal solution is impregnated into the graphite substrate of the graphite roller sleeve by a vacuum pressure impregnation method. After medium and high temperature heat treatment, a ceramic protective film is formed on the surface of the graphite substrate. However, the ceramic protective film only covers the surface of the graphite substrate, and the graphite roller sleeve needs to be used in a high temperature environment. The thermal expansion coefficient of the ceramic protective film and the thermal expansion coefficient of the graphite material are quite different. The ceramic protective film is prone to partial peeling, and loses the anti-oxidation protection effect on the graphite roller sleeve, and cannot meet the requirements of long-term use of the graphite roller sleeve in a high temperature environment.

[0005] 2. Use phosphate solution to impregnate graphite roller sleeves: Use phosphate solution, such as aluminum dihydrogen phosphate, magnesium dihydrogen phosphate (sodium), etc. as impregnating agent, and use vacuum pressure impregnation method to impregnate phosphate solution into graphite roller sleeve substrate. PO4 in phosphate is a phosphorus oxygen tetrahedron structure, which is the basic structural unit for forming phosphorus oxygen glass and has a layered structure. The phosphate structure is relatively stable at room temperature, but when the ambient temperature exceeds 900℃, the phosphate will crack, and the phosphorus element will be separated in the form of P2O5. Phosphoric acid will be generated in a hydrogen-containing environment and at a certain dew point temperature, and it will contact with the nickel on the surface of the adjacent high-temperature alloy roller core to react and generate nickel phosphate, that is, the metal roller core is corroded. Therefore, graphite roller sleeves used in high-temperature environments cannot use phosphorus-containing materials as antioxidants.

[0006] 3. Polycarbosilane, a polymer material, is used as an impregnating agent to impregnate the graphite roller sleeve substrate and treat it at high temperature to obtain a SiC ceramic protective layer on the surface and inside of the graphite roller sleeve substrate that can resist high-temperature oxidation. Polycarbosilane, a polymer material, is a new material that is difficult to obtain and very expensive, and cannot be used on a large scale in strip steel production lines. Summary of the invention

[0007] The object of the present invention is to provide a phosphorus-free impregnation method for a graphite roller sleeve, which can uniformly adhere an aluminum silicate anti-oxidation protective film on the surface and inside the pores of the graphite roller sleeve, thereby improving the high-temperature anti-oxidation performance of the graphite roller sleeve.

[0008] The present invention is achieved in that:

[0009] A phosphorus-free impregnation method for a graphite roller sleeve comprises the following steps:

[0010] Step 1: Using silica sol as a matrix, adding α-alumina micropowder and a dispersant to form a phosphorus-free antioxidant impregnation solution;

[0011] Step 2: heating the phosphorus-free antioxidant soaking solution;

[0012] Step 3: roughening the surface of the graphite roller sleeve and heating the graphite roller sleeve;

[0013] Step 4: After the impregnation tank is evacuated, a phosphorus-free antioxidant impregnation solution is injected, and the graphite roller sleeve is impregnated with the phosphorus-free antioxidant impregnation solution under pressure, so that silicon and aluminum oxide in the phosphorus-free antioxidant impregnation solution fully penetrate into the interior of the graphite roller sleeve through the pores, and an aluminum silicate antioxidant protective film is formed on the surface of the graphite roller sleeve;

[0014] Step 5: Take out and cool the graphite roller sleeve;

[0015] Step 6: Repeat steps 2 to 4 to complete the second impregnation of the graphite roller sleeve;

[0016] Step 7: Take out the graphite roller sleeve and cure the aluminum silicate anti-oxidation protective film at medium temperature so that the aluminum silicate anti-oxidation protective film is evenly attached to the inside and surface of the pores of the graphite roller sleeve.

[0017] In the step 1, the phosphorus-free antioxidant impregnation solution includes, by mass percentage, 0.5-1.5% of α-alumina micropowder, 0.01-0.05% of dispersant and the remainder of silica sol.

[0018] The particle size of the α-alumina micropowder is 500-1000 meshes.

[0019] In the step 2, the heating temperature of the phosphorus-free antioxidant impregnation solution is 80-150°C.

[0020] The volume density of the graphite roller sleeve is 1.74-1.78 g / cm3 , the porosity is 7-14%.

[0021] In the step 3, the heating temperature of the graphite roller sleeve is higher than the temperature of the phosphorus-free antioxidant impregnation solution, and the heating temperature of the graphite roller sleeve is 180-300°C.

[0022] In the step 4, the vacuum degree in the impregnation tank is 0.05-0.1 MPa, and the pressure of the pressurized impregnation is 0.3-0.8 MPa.

[0023] In the step 4, the immersion time is 1-2 hours.

[0024] In the step 7, the curing temperature of the aluminum silicate anti-oxidation protective film is 200-300° C., and the curing time is 8-12 hours.

[0025] In the step 7, the oxidation weight loss rate of the aluminum silicate anti-oxidation protective film in a high temperature environment is 28-32%.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] 1. The present invention adopts silica sol as the basic material, which has strong permeability, is conducive to the full penetration of silicate and silicon oxide into the graphite matrix through the pores, ensures that the aluminum silicate anti-oxidation protective film is evenly attached to the surface and pores of the graphite matrix, has a low oxidation weight loss rate in high-temperature air, and the formed aluminum silicate anti-oxidation protective film has a certain elasticity, which can adapt to the difference in thermal expansion coefficient between the aluminum silicate anti-oxidation protective film and the graphite roller sleeve under high-temperature working environment.

[0028] 2. The present invention adopts ultrafine α-alumina powder and dispersant to synthesize phosphorus-free antioxidant impregnation liquid, which can improve the structural stability of aluminum silicate antioxidant protective film in high temperature environment. While improving the high temperature antioxidant performance of graphite roller sleeve, it avoids the problem of phosphorus element in the prior art phosphate antioxidant corroding the metal roller core at high temperature, thereby increasing the service life of the metal roller core and graphite roller sleeve and improving the production efficiency of the silicon steel unit.

[0029] 3. The present invention heats the graphite roller sleeve after the surface texturing to reduce the wetting angle of the pore surface in the graphite roller sleeve, thereby reducing the resistance of the impregnating material (i.e., silicon and aluminum oxide) to penetrate into the pores of the graphite roller sleeve and increasing the penetration of the impregnating material, thereby forming a stable coating effect.

[0030] 4. The present invention heats the phosphorus-free antioxidant impregnation liquid to make it have good fluidity, and at the same time adjusts the pressure in the impregnation tank so that the graphite roller sleeve is impregnated under medium temperature and pressure, which can effectively improve the impregnation effect.

[0031] The present invention prepares a phosphorus-free antioxidant impregnation liquid by adding alpha alumina powder and a dispersant to silica sol, and impregnates the graphite roller sleeve under a medium-temperature pressurized environment, so that silicon and alumina fully penetrate into the pores of the graphite roller sleeve, and an aluminum silicate antioxidant protective film is uniformly attached to the surface of the graphite roller sleeve and the inside of the pores, thereby effectively improving the high-temperature antioxidant performance of the graphite roller sleeve, meeting the requirements of long-term stable use in a high-temperature working environment, and meeting the needs of large-scale production and use on a silicon steel production line. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 The present invention is a flow chart of the phosphorus-free impregnation method of the graphite roller sleeve. DETAILED DESCRIPTION

[0033] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments.

[0034] Please see attached Figure 1 , a phosphorus-free impregnation method for a graphite roller sleeve comprises the following steps:

[0035] Step 1: Using silica sol as a matrix, adding α-alumina micropowder and dispersant, and completing after sufficient mixing to form a phosphorus-free antioxidant impregnation solution.

[0036] Silica sol is a colloidal solution of multi-molecular polymers of silica. When silica sol loses water, monomer silica gradually polymerizes into polysilicic acid. As the water evaporates, the molecular weight of the colloidal increases, and finally a coating with a network structure is formed. It has a certain elasticity and can effectively prevent the film from cracking, so as to adapt to the difference in thermal expansion rate between it and the graphite matrix. In addition, silica sol has strong penetration, and can penetrate silicon and alumina into the inside of the graphite roller sleeve through the pores on the graphite roller sleeve.

[0037] α-alumina powder is a low-temperature phase-transition calcined ultrafine particle ceramic material with high melting point, good thermal stability, high hardness, good wear resistance, high mechanical strength, good electrical insulation and corrosion resistance. The addition of trace α-alumina powder in silica sol can improve the adhesion of silica sol mixture on the graphite surface and improve the strength of the sol film after consolidation, so that the surface strength and wear resistance of the graphite substrate after impregnation are further improved.

[0038] Since the amount of α-alumina powder added to the silica sol is very small, the uniformity of mixing the trace α-alumina powder in the silica sol can be effectively improved by adding a certain proportion of dispersant. The dispersant can be a polymer dispersant. The polymer dispersant has a large molecular weight and can be adsorbed on the surface of solid particles. Its long polymer chain is fully extended in the medium to form an adsorption layer with a thickness of several nanometers to tens of nanometers. The resulting steric hindrance effect can effectively prevent the particles from aggregating with each other. In addition to the steric hindrance effect, polymer dispersants also have an electrostatic stabilization effect. When the particles are far away, the double electric layer repulsion plays a dominant role; when the particles are close, the steric hindrance particles are close, and the trace α-alumina powder is fully and evenly mixed in the silica sol through the electrostatic stabilization effect and steric hindrance.

[0039] Calculated by mass percentage, the phosphorus-free antioxidant impregnation solution includes 0.5-1.5% of α-alumina micropowder, 0.01-0.05% of dispersant and the remainder of silica sol.

[0040] The particle size of the α-alumina micropowder is 500-1000 meshes.

[0041] Step 2: Heat the phosphorus-free antioxidant impregnation solution. Heating can improve the fluidity of the phosphorus-free antioxidant impregnation solution and achieve the best impregnation and penetration effect.

[0042] The heating temperature of the phosphorus-free antioxidant impregnation liquid is 80-150°C, preferably 80-100°C, so that the phosphorus-free antioxidant impregnation liquid maintains good fluidity. Since the phosphorus-free antioxidant impregnation liquid contains α-alumina powder, excessively high heating temperature will reduce the fluidity of the phosphorus-free antioxidant impregnation liquid and even cause it to solidify.

[0043] Step 3: Roughen the surface of the graphite roller sleeve, clean the surface of the graphite roller sleeve, and heat the graphite roller sleeve. Roughening the surface of the graphite roller sleeve can facilitate the penetration and adhesion of silicon and aluminum oxide, increase the temperature of the graphite roller sleeve, reduce the wetting angle of the impregnation interface, and facilitate the penetration of the graphite roller sleeve by the phosphorus-free antioxidant impregnation liquid.

[0044] The volume density of the graphite roller sleeve is 1.74-1.78 g / cm 3 , the porosity is 7-14%.

[0045] The heating temperature of the graphite roller sleeve is higher than the temperature of the phosphorus-free antioxidant impregnation liquid, and the heating temperature of the graphite roller sleeve is 180-300°C, preferably 180-250°C. After heating, the internal pores of the graphite roller sleeve expand and become larger, which is conducive to the more complete intrusion of the phosphorus-free antioxidant impregnation liquid and improves the impregnation effect. At the same time, considering that the temperature may drop during the process of the graphite roller sleeve being moved to the impregnation tank after heating, the temperature of the graphite roller sleeve may be slightly higher than the temperature of the phosphorus-free antioxidant impregnation liquid. Therefore, the heating temperature of the graphite roller sleeve matches that of the phosphorus-free antioxidant impregnation liquid, that is, the temperature difference between the graphite roller sleeve and the phosphorus-free antioxidant impregnation liquid cannot be too large. If the temperature of the graphite roller sleeve is too high, the phosphorus-free antioxidant impregnation liquid may be heated and solidified during the impregnation process, which is not conducive to the penetration of the impregnated material in the phosphorus-free antioxidant impregnation liquid.

[0046] Step 4: After the impregnation tank is evacuated, the phosphorus-free antioxidant impregnation liquid is injected, and the graphite roller sleeve is impregnated with the phosphorus-free antioxidant impregnation liquid under pressure, so that the silicon and aluminum oxide in the phosphorus-free antioxidant impregnation liquid fully penetrate into the interior of the graphite roller sleeve through the pores, and an aluminum silicate antioxidant protective film is formed on the surface of the graphite roller sleeve. The oxidation reaction of the graphite material occurs on the surface and internal microporous surface of the graphite roller sleeve. After the graphite roller sleeve is impregnated and infiltrated under high pressure in the phosphorus-free antioxidant impregnation liquid, the phosphorus-free antioxidant impregnation liquid can penetrate into the pores of the graphite roller sleeve and form a protective film on the surface of the pores.

[0047] The vacuum degree in the impregnation tank is 0.05-0.1MPa, and the pressure of the pressurized impregnation is 0.3-0.8MPa. The impregnation pressure can be adjusted according to the actual fluidity of the phosphorus-free antioxidant impregnation solution and the penetration effect of the phosphorus-free antioxidant impregnation solution on the graphite roller sleeve. The impregnation tank has a heat preservation function, which keeps the graphite roller sleeve at a medium temperature during the pressurized impregnation process and improves the impregnation effect.

[0048] The impregnation time is 1-2 hours, ensuring that the silicon and aluminum oxide in the phosphorus-free antioxidant impregnation solution fully penetrate into the interior of the graphite roller sleeve through the pores.

[0049] Step 5: Remove and cool the graphite roller sleeve.

[0050] Step 6: Repeat steps 2 to 4 to complete the second impregnation of the graphite roller sleeve.

[0051] Step 7: Take out the graphite roller sleeve, and cure the aluminum silicate anti-oxidation protective film inside and on the surface of the graphite roller sleeve in a medium temperature environment, so that the aluminum silicate anti-oxidation protective film is evenly attached to the inside and surface of the pores of the graphite roller sleeve.

[0052] The curing temperature of the aluminum silicate anti-oxidation protective film is 200-300° C., and the curing time is 8-12 hours, preferably curing at 250° C. for 12 hours.

[0053] The oxidation weight loss rate of the aluminum silicate anti-oxidation protective film in a high temperature environment is 28-32%, thereby effectively improving the service life of the metal roller core and the graphite roller sleeve, and improving the production efficiency of the silicon steel unit. The test method of the oxidation weight loss rate is: place a graphite roller sleeve sample with a uniformly attached aluminum silicate anti-oxidation protective film in a constant temperature heating furnace at 1100°C, the size of the graphite roller sleeve sample is φ30*30cm, dry air is introduced into the heating furnace at a flow rate of 2 liters / minute for 2 hours, and the weight change rate of the ink roller sleeve sample before and after heating is calculated, which is the oxidation weight loss rate of the aluminum silicate anti-oxidation protective film.

[0054] Embodiment 1:

[0055] This embodiment is applied to a volume density of 1.77 g / cm 3 , graphite roller sleeve with a porosity of 7%.

[0056] Step 1: With silica sol as the matrix, 0.5% of α-alumina powder and 0.03% of dispersant are added by mass percentage to form a phosphorus-free antioxidant impregnation solution, wherein the particle size of the α-alumina powder is 500 meshes.

[0057] Step 2: Heat the phosphorus-free antioxidant impregnation solution to 80° C. to improve the fluidity of the phosphorus-free antioxidant impregnation solution.

[0058] Step 3: After the surface of the graphite roller sleeve is roughened and cleaned, the graphite roller sleeve is heated to 180°C to reduce the wetting angle of the impregnation interface, which is conducive to the penetration of the phosphorus-free antioxidant impregnation liquid into the graphite roller sleeve.

[0059] Step 4: After the impregnation tank is evacuated to 0.05MPa, the phosphorus-free antioxidant impregnation liquid is injected, and the phosphorus-free antioxidant impregnation liquid is pressurized to 0.3MPa for impregnating the graphite roller sleeve. The impregnation time is 2h, so that the silicon and aluminum oxide in the phosphorus-free antioxidant impregnation liquid penetrate into the interior of the graphite roller sleeve through the pores and form an aluminum silicate antioxidant protective film on the surface of the graphite roller sleeve.

[0060] Step 5: Take out and cool the graphite roller sleeve naturally.

[0061] Step 6: Repeat steps 2 to 4 to complete the second impregnation of the graphite roller sleeve.

[0062] Step 7: Take out the graphite roller sleeve and cure the aluminum silicate anti-oxidation protective film at 250°C for 12 hours to make the aluminum silicate anti-oxidation protective film evenly adhere to the inside and surface of the pores of the graphite roller sleeve.

[0063] The oxidation weight loss rate of the aluminum silicate anti-oxidation protective film of the graphite roller sleeve prepared in this embodiment is 31%.

[0064] Embodiment 2:

[0065] This embodiment is applied to a volume density of 1.78 g / cm 3 , graphite roller sleeve with a porosity of 8%.

[0066] Step 1: With silica sol as the matrix, 0.8% of α-alumina powder and 0.03% of dispersant are added by mass percentage to form a phosphorus-free antioxidant impregnation solution, wherein the particle size of the α-alumina powder is 800 meshes.

[0067] Step 2: Heat the phosphorus-free antioxidant impregnation solution to 90° C. to improve the fluidity of the phosphorus-free antioxidant impregnation solution.

[0068] Step 3: After the surface of the graphite roller sleeve is roughened and cleaned, the graphite roller sleeve is heated to 200° C. to reduce the wetting angle of the impregnation interface, which is conducive to the penetration of the phosphorus-free antioxidant impregnation liquid into the graphite roller sleeve.

[0069] Step 4: After the impregnation tank is evacuated to 0.1MPa, the phosphorus-free antioxidant impregnation liquid is injected, and the phosphorus-free antioxidant impregnation liquid is pressurized to 0.3MPa for impregnating the graphite roller sleeve. The impregnation time is 2h, so that the silicon and aluminum oxide in the phosphorus-free antioxidant impregnation liquid penetrate into the interior of the graphite roller sleeve through the pores and form an aluminum silicate antioxidant protective film on the surface of the graphite roller sleeve.

[0070] Step 5: Take out and cool the graphite roller sleeve naturally.

[0071] Step 6: Repeat steps 2 to 4 to complete the second impregnation of the graphite roller sleeve.

[0072] Step 7: Take out the graphite roller sleeve, and cure the aluminum silicate antioxidant protective film at a medium temperature of 250°C for 12 hours, so that the aluminum silicate antioxidant protective film is evenly attached to the inside and surface of the pores of the graphite roller sleeve.

[0073] The oxidation weight loss rate of the aluminum silicate anti-oxidation protective film of the graphite roller sleeve prepared in this embodiment is 28%.

[0074] Embodiment 3:

[0075] This embodiment is applied to a volume density of 1.76 g / cm 3 , graphite roller sleeve with a porosity of 11%.

[0076] Step 1: With silica sol as the matrix, 1.0% of α-alumina powder and 0.03% of dispersant are added by mass percentage to form a phosphorus-free antioxidant impregnation solution, wherein the particle size of the α-alumina powder is 500 meshes.

[0077] Step 2: Heat the phosphorus-free antioxidant impregnation solution to 90° C. to improve the fluidity of the phosphorus-free antioxidant impregnation solution.

[0078] Step 3: After the surface of the graphite roller sleeve is roughened and cleaned, the graphite roller sleeve is heated to 190°C to reduce the wetting angle of the impregnation interface, which is conducive to the penetration of the phosphorus-free antioxidant impregnation liquid into the graphite roller sleeve.

[0079] Step 4: After the impregnation tank is evacuated to 0.05MPa, the phosphorus-free antioxidant impregnation liquid is injected, and the phosphorus-free antioxidant impregnation liquid is pressurized to 0.3MPa for impregnating the graphite roller sleeve. The impregnation time is 1 hour, so that the silicon and aluminum oxide in the phosphorus-free antioxidant impregnation liquid penetrate into the interior of the graphite roller sleeve through the pores, and form an aluminum silicate antioxidant protective film on the surface of the graphite roller sleeve.

[0080] Step 5: Take out and cool the graphite roller sleeve naturally.

[0081] Step 6: Repeat steps 2 to 4 to complete the second impregnation of the graphite roller sleeve.

[0082] Step 7: Take out the graphite roller sleeve, and cure the aluminum silicate antioxidant protective film at a medium temperature of 250°C for 12 hours, so that the aluminum silicate antioxidant protective film is evenly attached to the inside and surface of the pores of the graphite roller sleeve.

[0083] The oxidation weight loss rate of the aluminum silicate anti-oxidation protective film of the graphite roller sleeve prepared in this embodiment is 32%.

[0084] Embodiment 4:

[0085] This embodiment is applied to a volume density of 1.73 g / cm 3 , graphite roller sleeve with a porosity of 14%.

[0086] Step 1: With silica sol as the matrix, 1.5% of α-alumina powder and 0.03% of dispersant are added by mass percentage to form a phosphorus-free antioxidant impregnation solution, wherein the particle size of the α-alumina powder is 500 meshes.

[0087] Step 2: Heat the phosphorus-free antioxidant impregnation solution to 80° C. to improve the fluidity of the phosphorus-free antioxidant impregnation solution.

[0088] Step 3: After the surface of the graphite roller sleeve is roughened and cleaned, the graphite roller sleeve is heated to 250°C to reduce the wetting angle of the impregnation interface, which is conducive to the penetration of the phosphorus-free antioxidant impregnation liquid into the graphite roller sleeve.

[0089] Step 4: After the impregnation tank is evacuated to 0.3MPa, the phosphorus-free antioxidant impregnation liquid is injected, and the phosphorus-free antioxidant impregnation liquid is pressurized to 0.4MPa for impregnating the graphite roller sleeve. The impregnation time is 1h, so that the silicon and aluminum oxide in the phosphorus-free antioxidant impregnation liquid penetrate into the interior of the graphite roller sleeve through the pores, and form an aluminum silicate antioxidant protective film on the surface of the graphite roller sleeve.

[0090] Step 5: Take out and cool the graphite roller sleeve naturally.

[0091] Step 6: Repeat steps 2 to 4 to complete the second impregnation of the graphite roller sleeve.

[0092] Step 7: Take out the graphite roller sleeve and cure the aluminum silicate anti-oxidation protective film at 250°C for 12 hours to make the aluminum silicate anti-oxidation protective film evenly adhere to the inside and surface of the pores of the graphite roller sleeve.

[0093] The oxidation weight loss rate of the aluminum silicate anti-oxidation protective film of the graphite roller sleeve prepared in this embodiment is 31%.

[0094] The above are only preferred embodiments of the present invention and are not intended to limit the protection scope of the present invention. Therefore, any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A phosphorus-free impregnation method for a graphite roller sleeve, characterized in that: The following steps are involved: Step 1: Using silica sol as a matrix, adding α-alumina micropowder and a dispersant to form a phosphorus-free antioxidant impregnation solution; Step 2: heating the phosphorus-free antioxidant soaking solution; Step 3: roughening the surface of the graphite roller sleeve and heating the graphite roller sleeve; Step 4: After the impregnation tank is evacuated, a phosphorus-free antioxidant impregnation solution is injected, and the graphite roller sleeve is impregnated with the phosphorus-free antioxidant impregnation solution under pressure, so that silicon and aluminum oxide in the phosphorus-free antioxidant impregnation solution fully penetrate into the interior of the graphite roller sleeve through the pores, and an aluminum silicate antioxidant protective film is formed on the surface of the graphite roller sleeve; Step 5: Take out and cool the graphite roller sleeve; Step 6: Repeat steps 2 to 4 to complete the second impregnation of the graphite roller sleeve; Step 7: Take out the graphite roller sleeve, and cure the aluminum silicate anti-oxidation protective film at medium temperature, so that the aluminum silicate anti-oxidation protective film is evenly attached to the inside and surface of the pores of the graphite roller sleeve; In the step 1, the phosphorus-free antioxidant impregnation solution includes, by mass percentage, 0.5-1.5% of α-alumina micropowder, 0.01-0.05% of a dispersant and the remainder of silica sol; The particle size of the α-alumina micropowder is 500-1000 mesh; in, In step 2, the heating temperature of the phosphorus-free antioxidant impregnation solution is 80-150° C.; In step 3, the heating temperature of the graphite roller sleeve is higher than the temperature of the phosphorus-free antioxidant impregnation solution, and the heating temperature of the graphite roller sleeve is 180-300° C.; In step 4, the vacuum degree in the impregnation tank is 0.05-0.1 MPa, and the pressure of the pressurized impregnation is 0.3-0.8 MPa.

2. The phosphorus-free impregnation method of graphite roller sleeve according to claim 1, characterized in that: The volume density of the graphite roller sleeve is 1.74-1.78 g / cm 3 , the porosity is 7-14%.

3. The phosphorus-free impregnation method of graphite roller sleeve according to claim 1, characterized in that: In the step 4, the immersion time is 1-2 hours.

4. The phosphorus-free impregnation method of graphite roller sleeve according to claim 1, characterized in that: In the step 7, the curing temperature of the aluminum silicate anti-oxidation protective film is 200-300° C., and the curing time is 8-12 hours.

5. The phosphorus-free impregnation method of graphite roller sleeve according to claim 1, characterized in that: In the step 7, the oxidation weight loss rate of the aluminum silicate anti-oxidation protective film in a high temperature environment is 28-32%.

Citation Information

Patent Citations

  • Dipping treatment solution for fire resistive material and carbon material

    CN101148366A

  • Surface treatment method for improving high temperature oxidation resistance of silicon steel graphite roller sleeve

    CN104045376A